2005
DOI: 10.1016/j.ymthe.2005.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Viral-Mediated Transduction to the Lung Airway Epithelium with the Anti-inflammatory Cationic Lipid Dexamethasone–Spermine

Abstract: We formulated adenovirus (AdV) vectors with cationic steroid liposomes containing dexamethasone-spermine (DS)/dioleoylphosphatidylethanolamine (DOPE) in an effort to overcome the lack of apically expressed AdV vector receptors on airway epithelial cells and to reduce the inflammation associated with AdV vector exposure. An AdV vector (1 to 2.5 x 10(11) genome copies) expressing human placental alkaline phosphatase or beta-galactosidase (LacZ) was delivered alone or complexed with DS/DOPE, DC-Chol/DOPE, or dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…At least partial activity described for DS may be expected from disubstituted DS (D2S). DS and D2S (20,22,37) share some structural and functional properties with squalamine, a membrane-active cationic steroid antibiotic (CSA) (34), and some previously described cholic acid antimicrobial derivatives (23,42). Squalamine, first isolated from tissues of the dogfish shark, and its analogues with different polyamines added to the 3-keto group by reductive amination (29) effectively kill different strains of bacteria, but mammals appear not to produce cationic steroids as antimicrobial factors (17).…”
mentioning
confidence: 99%
“…At least partial activity described for DS may be expected from disubstituted DS (D2S). DS and D2S (20,22,37) share some structural and functional properties with squalamine, a membrane-active cationic steroid antibiotic (CSA) (34), and some previously described cholic acid antimicrobial derivatives (23,42). Squalamine, first isolated from tissues of the dogfish shark, and its analogues with different polyamines added to the 3-keto group by reductive amination (29) effectively kill different strains of bacteria, but mammals appear not to produce cationic steroids as antimicrobial factors (17).…”
mentioning
confidence: 99%
“…We have also shown that D 2 S effectively prevented LPS from causing upregulation of IL-8 expression in human neutrophils, which are a primary source of production of proinflammatory cytokines (including IL-8 and TNF-␣) and can be induced by bacterial LPS (Bucki et al, 2008). This suppression of bacterial-mediated inflammation is probably because of the interaction of D 2 S with LPS; however, because this lipid has a base glucocorticoid structure, it may be expected that pharmacological activity is providing additional anti-inflammatory activity through cortisol receptor activation (Price et al, 2005). This is evidenced by the complete inactivation of a highly inflammatory LPS concentration by D 2 S, but additional studies are needed to separate pharmacological activity from the prevention of LPS-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…DS has been shown previously to exhibit anti-inflammatory activity in an in vivo mouse intraperitoneal thioglycollate challenge model based on neutrophil infiltration and has been shown to condense and deliver plasmid DNA enabling in vitro transfection of plasmid DNA. DS has also been shown to improve airway targeting, attenuate vector-induced inflammation, and facilitate readministration in vivo when formulated with adenovirus vectors (Price et al, 2005(Price et al, , 2007. D 2 S has not been examined previously; therefore, lipofection activity was assessed as an individual component and with DS to establish potential synergistic activity in mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…21 We have previously shown that the formulation of AdV vector with liposomes comprised of the antiinflammatory cationic lipid dexamethasone-spermine (DS) and the neutral lipid dioleoylphosphatidylethanolamine (DOPE), when delivered to the lung, targets transgene expression to the conducting airway epithelial cells and significantly reduces cellular infiltration, compared to delivery of AdV vector alone. 22 Improved targeting of AdV vector to the conducting airway epithelial cells by DS was due to the physical-chemical properties of liposomes in general, while the reduction in cellular infiltration was due to the anti-inflammatory properties of DS. 22 DS was also anti-inflammatory in a murine intraperitoneal thioglycollate challenge model and reduced IFNg production at day 1 following plasmid lipoplex delivery to lung.…”
Section: Introductionmentioning
confidence: 99%
“…22 Improved targeting of AdV vector to the conducting airway epithelial cells by DS was due to the physical-chemical properties of liposomes in general, while the reduction in cellular infiltration was due to the anti-inflammatory properties of DS. 22 DS was also anti-inflammatory in a murine intraperitoneal thioglycollate challenge model and reduced IFNg production at day 1 following plasmid lipoplex delivery to lung. 23 In the current study, our goal was to investigate the nature of the immune response, both pulmonary and systemic, to AdV vector delivered in various formulations.…”
Section: Introductionmentioning
confidence: 99%